Eksploitasi Siber dan Pertanggungjawaban Negara di Asia Tenggara: Tinjauan Viktimologis dalam Kerangka Hukum Internasional - Feby Reski Utami; Litya Surisdani Anggraeniko; Shaifullah Shaifullah (Southeast Asian Journal of Victimology, 2026)
The practice of online scams in Cambodia has evolved into cyber slavery, involving human trafficking and forced labor. This study aims to analyze this phenomenon through a victimological perspective and examine state responsibility under international law. Employing a normative juridical method with statutory, conceptual, case study, comparative law, and victimological approaches, this research evaluates relevant international instruments. Findings indicate that scam compound operations fulfill the elements of trafficking and forced labor, causing primary, secondary, and moral injury to victims due to the weak application of the non-punishment principle. Legally, the state has failed to fulfill its due diligence obligations and the 4P framework. This study recommends strengthening regional legal harmonization, establishing an ASEAN rapid response mechanism, and adopting a victim-centered justice approach, as implemented in the UK's Modern Slavery Act, to enforce state responsibility in eradicating cyber slavery in Southeast Asia.